2014
DOI: 10.1016/j.plantsci.2014.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated O3 exposure on seed yield, N concentration and photosynthesis of nine soybean cultivars (Glycine max (L.) Merr.) in Northeast China

Abstract: a b s t r a c tNine soybean cultivars widely cultivated in Northeast China were investigated in present study to assess their O 3 sensitivities on the basis of the response of photosynthesis and seed yield to ambient and future ozone (O 3 ) concentrations, and determine whether the effects of O 3 vary with the developmental stages (flowering and seed filling stages). Relative to charcoal-filtered air (CF), elevated O 3 concentration (E-O 3 , ambient air + 40 ppb) significantly reduced soybean yields by 40%, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…A variety of detrimental changes at the biochemical, physiological and molecular levels have been demonstrated in conifers and deciduous trees (Koch et al, 1998;Kopper and Lindroth, 2003;Richet et al, 2011Richet et al, , 2012Zhang et al, 2014a). Experimental evidence indicates that not only species but also cultivars, genotypes and clones, show different sensitivity to O 3 (Calatayud et al, 2011;Castagna et al, 2015;Dumont et al, 2014;H€ aiki€ o, 2009;Paoletti and Grulke, 2010;Zhang et al, 2012Zhang et al, , 2014c.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of detrimental changes at the biochemical, physiological and molecular levels have been demonstrated in conifers and deciduous trees (Koch et al, 1998;Kopper and Lindroth, 2003;Richet et al, 2011Richet et al, , 2012Zhang et al, 2014a). Experimental evidence indicates that not only species but also cultivars, genotypes and clones, show different sensitivity to O 3 (Calatayud et al, 2011;Castagna et al, 2015;Dumont et al, 2014;H€ aiki€ o, 2009;Paoletti and Grulke, 2010;Zhang et al, 2012Zhang et al, , 2014c.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al (2014) reported that leaf ozone injury was widespread in the Beijing area, with 28 different species (including trees, shrubs, and crops) showing typical ozone symptoms. Results from Open Top Chamber experiments in Northeast China suggest that mean ozone concentrations of 58.6 ppb significantly reduce yield by 40% (with a range of 32e46%) in eight soybean genotypes (Zhang et al, 2014). A modeling study suggested that ozone reduced yield of four important crops (wheat, rice, maize and soybean) in China by 1e23% in the 1990s, and predicted further reductions (between 7 and 64%) for 2020 (Van Dingenen et al, 2009;Wang and Mauzerall, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…China, as an important country in East Asia, has experienced phenomenally rapid economic expansion in the past several decades, but it also resulted in more emissions of O 3 precursors such as NO x due to increased consumption of fossil fuels (Wang et al, 2007). High levels of O 3 had been observed in many areas and cities of China (Tang et al, 2009;Wang et al, 2009Wang et al, , 2012Zhang et al, 2014;Zheng et al, 2011), especially in Beijing. According to Ding et al (2008) from aircraft observations over Beijing, the O 3 concentration was increasing approximately at a rate of 2% per year from 1995 to 2005.…”
Section: Introductionmentioning
confidence: 99%